Utilization Of Social Media And Online Marketplace For The Development Of Marketing Of Small And Medium Enterprises (Smes) In The Clothing Industry (A Study On Clothing Companies In Malang) - Umar Syarifuddien Sjadja’ah; Sopiah Sopiah; Ery Tri Djatmika Rudijanto Wahyu Wardhana (Green Publisher Indonesia, 2024)
Micro, Small and Medium Enterprises (MSMEs) have an important role in the Indonesian economy. Many studies on MSMEs are expected to improve the quality of the MSMEs themselves. Meanwhile, social media and online marketplaces are increasingly familiar to Indonesians who are technology and internet literate. Research on MSMEs marketing with social media and online marketplaces is always needed along with rapid technological advances. Therefore, researchers try to discuss how MSMEs in the fashion or clothing company category in Malang City utilize social media and online marketplaces for their marketing development. This research was conducted using a qualitative method with a phenomenological approach. Phenomenology is a study intended to seek the essence or meaning of a phenomenon experienced by several research individuals. This research involved four micro-scale clothing MSMEs in Malang City. From the results of the interviews, it was found that all clothing MSME players in Malang City have used social media as a marketing tool. In fact, all clothing MSMEs make social media their main marketing tool. However, the online marketplace is still not used optimally. The obstacles faced by UMKM clothing companies are limited capital, human resources, and Marketing using social media can still be maximized again by recruiting social media specialists and influencers.